The Effect of Digital Literacy and Motivation on Teacher’s Performance - Nugraha, Filipus Chinmi Adin; Ahyani, Nur; Rohana, Rohana (Journal of Social Work and Science Education, 2024)
This research aims to know and examine: (1) The effect of digital literacy on teacher performance; (2) The effect of motivation on teacher performance; and (3) The effect of digital literacy and motivation together on teacher performance. This research is quantitative research with an ex post facto approach. This research was conducted in public and private junior high schools in Ilir Timur 1 Palembang District with a population of 240 teachers, and a random sample of 150 people was taken. The data collection technique used a questionnaire. The validity test uses construction validity and content validity, while the reliability test uses Cronbach’s Alpha. The analysis requirements test uses normality test, linearity test, multicollinearity test, and heteroscedasticity test, and the data is analyzed using multiple linear regression techniques. The results showed that digital literacy, motivation, and teacher performance can still be said to be sufficient, there is a positive and significant influence between digital literacy and motivation together on teacher performance by 65.2% while 34.8% is determined by other factors not mentioned in this study.